Lead induced structural and functional damage and microbiota dysbiosis in the intestine of crucian carp (Carassius auratus) - Liu, Haisu; Zhang, Hang; Yu, Qianxun; Zhang, Sanshan; Tu, Xiao; Zhuang, Fenghong; Fu, Shengli (Frontiers in Microbiology, 2023)
Lead (Pb) is a hazardous pollutant in water environments that can cause significant damage to aquatic animals and humans. In this study, crucian carp (Carassius auratus) were exposed to waterborne Pb for 96 hours, then histopathological analysis, quantitative qPCR analysis, and 16S high-throughput sequencing were performed to explore the effects of Pb on intestinal bioaccumulation, structural damage, oxidative stress, immune response and microbiota imbalance of C. auratus. After Pb exposure, the intestinal morphology was obviously damaged, including significantly increasing the thickness of the intestinal wall and the number of goblet cells, and reducing the depth of intestinal crypts. Pb exposure reduced the mRNA expressions of Claudin-7 and villin-1, while significantly elevated the level of GST, GSH, CAT, IL-8, IL-10, IL-1 and TNF-α. Furthermore, 16S rRNA analysis showed that the shannon and simpson index decreased at 48 h after Pb exposure, and the abundance of pathogenic bacteria (Erysipelotrichaceae, Weeksellaceae, Vibrionaceae) increased after Pb exposure. In addition, the correlation network analysis found that Proteobacteria were negatively correlated with Firmicutes and positively correlated with Bacteroidetes. Functional prediction analysis of bacteria speculated that the change of intestinal microbiota led to the PPAR signaling pathway and peroxisome function of crucian carp intestine were increased, while the immune system and membrane transport function were decreased. Finally, Canonical correlation analysis (CCA) found that there were correlations between the intestinal microbiota, morphology, antioxidant factors, and immune factors of crucian carp after Pb exposure. Taken together, our results demonstrated that intestinal flora dysbiosis, morphological disruption, oxidative stress and immune injury are involved in the toxic damage of Pb exposure to the crucian carp’s intestine structural and function. Meanwhile, Pb exposure rapidly increased the abundance of pathogenic bacteria, leading to intestinal disorders, further aggravating the damage of Pb to intestinal structure and function. These findings provide us a basis for the link between gut microbiome changes and heavy metal toxicity, and gut microbiota can be used as biomarkers for the evaluation of heavy metal pollution in the future.